Rebuilding the myocardial microenvironment to enhance mesenchymal stem cells-mediated regeneration in ischemic heart disease - Chu, Qing; Jiang, Xin; Xiao, Ying (Frontiers in Bioengineering and Biotechnology, 2024)
Mesenchymal stem cells (MSCs) are naturally-derived regenerative materials that exhibit significant potential in regenerative medicine. Previous studies have demonstrated that MSCs-based therapy can improve heart function in ischemia-injured hearts, offering an exciting therapeutic intervention for myocardial ischemic infarction, a leading cause of worldwide mortality and disability. However, the efficacy of MSCs-based therapies is significantly disturbed by the myocardial microenvironment, which undergoes substantial changes following ischemic injury.After the ischemic injury, blood vessels become obstructed and damaged, and cardiomyocytes experience ischemic conditions. This activates the hypoxia-induced factor 1 (HIF-1) pathway, leading to the rapid production of several cytokines and chemokines, including vascular endothelial growth factor (VEGF) and stromal-derived factor 1 (SDF-1), which are crucial for angiogenesis, cell migration, and tissue repair, but it is not sustainable. MSCs respond to these cytokines and chemokines by homing to the injured site and participating in myocardial regeneration.However, the deteriorated microenvironment in the injured myocardium poses challenges for cell survival, interacting with MSCs, and constraining their homing, retention, and migration capabilities, thereby limiting their regenerative potential. This review discusses how the deteriorated microenvironment negatively affects the ability of MSCs to promote myocardial regeneration. Recent studies have shown that optimizing the microenvironment through the promotion of angiogenesis can significantly enhance the efficacy of MSCs in treating myocardial infarction. This approach harnesses the full therapeutic potential of MSCs-based therapies for ischemic heart disease.